2013
DOI: 10.1021/ie4009259
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Longitudinal Permeability of Oil Palm Wood

Abstract: In this research, variations in longitudinal permeability of oil palm (Elaeis guineensis Jacq) wood were investigated. Panels were prepared from bark to pith with the study carried out on 3 parts of the transverse surface: outer, middle, and inner. Microscopic observations were done to determine the anatomical properties to establish its theoretical permeability using Poiseuille's equation. Results showed that the middle part of the transverse surface of oil palm wood had the highest theoretical, water, and ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Such transports are generally considered as being governed by laws similar to those in a porous medium with neutral structure. However, the permeability, although in principle an intrinsic parameter, was found to vary with the sample length [10][11][12][13][14], which suggests that some effect might affect the basic liquid transport in wood. Moreover, it was shown that subtle hydraulic mechanisms between adjacent vessels can foster water refilling in embolized xylems vessels [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Such transports are generally considered as being governed by laws similar to those in a porous medium with neutral structure. However, the permeability, although in principle an intrinsic parameter, was found to vary with the sample length [10][11][12][13][14], which suggests that some effect might affect the basic liquid transport in wood. Moreover, it was shown that subtle hydraulic mechanisms between adjacent vessels can foster water refilling in embolized xylems vessels [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the core samples were extracted with an alcohol–benzene mixture, and cleaned with massive reservoir brine until the pH value was 7, then dried at 60°C for 48 h. Afterwards, the cleaned reservoir brine was injected at a constant rate of 1 cm 3 /min by a positive displacement pump (ISCO 260D syringe pump) until the pressure drop became stable. The absolute permeability of the core ( k 0 ) was calculated using Darcy's law (Eq. ) k=μQL/AΔP where k is the permeability of the core, µ is the viscosity of the fluid, A is the cross‐sectional area of the core, Q is the flow rate of the working fluid, Δ P is the pressure drop and L is the length of the core.…”
Section: Methodsmentioning
confidence: 99%
“…Initially, the core samples were extracted with an alcohol-benzene mixture, and cleaned with massive reservoir brine until the pH value was 7, then dried at 60°C for 48 h. Afterwards, the cleaned reservoir brine was injected at a constant rate of 1 cm 3 /min by a positive displacement pump (ISCO 260D syringe pump) until the pressure drop became stable. The absolute permeability of the core (k 0 ) was calculated using Darcy's law [26]…”
Section: Core Flood Testsmentioning
confidence: 99%
“…Each specimen was tested three times to finally calculate the permeability. Then, the superficial permeability coefficient was calculated (Equations (2) and (3)) [32,33]. The superficial gas permeability coefficients (k g ) were corrected by the viscosity of air (µ = 1.81 × 10 −5 Pa s) for the calculation of the specific gas permeability (K g = k g µ).…”
Section: Gas Permeability Measurementmentioning
confidence: 99%